Instrumen Asesmen Kompetensi Literasi Membaca Setara PIRLS dengan Teks Muatan Kultural Edukatif di SEkolah dasar - Nurchasanah; Imroatul Mufidah; Titik Harsiati (Jurnal Penelitian Pendidikan IPA, 2023)
The objectives of this research and development are (1) to produce a product prototype of the PIRLS equivalent reading literacy competency assessment instrument with educative cultural content text for grade 6 elementary school students, (2) to test the PIRLS equivalent reading literacy competency assessment instrument with educative cultural content text for grade 6 elementary school students from the aspects of content validity, construct validity, Esay question reliability test, Objective question reliability test, difficulty level, and differentiability. This type of research and development uses the Borg & Gall model which consists of 10 stages. The data collected is qualitative and quantitative data. The data is related to content validity, construct validity, readability, and practicality of the assessment instrument as well as the practicality of the user manual. The collected data were analyzed with content validity (Gregory), Product Moment, and Cronbach's Alpha. Based on the results of the analysis and discussion, the results of the correlation person analysis for the overall r value of 30 items > r table for subject 28 the r table value is 0.361 with the acquisition of the smallest value of 0.383 and the largest of 0.724. In addition to the results of the limited subject test, the results of the analysis of the broad subject test using SPSS for windows version 26 software also showed the results that the person correlation value for the reading literacy competency assessment instrument from a total of 30 items obtained a calculated r value> r table for subjects 141 people the r table value of 0.361 with the acquisition of the smallest value of 0.439 and the largest value of 0.896. While the acquisition of the teacher response score is 0.882. So, based on these results it can be said that the product of the reading literacy competency assessment instrument equivalent to the Progress in International Reading Literacy Study with educational cultural content text is suitable for direct use for every grade 6 elementary school student.